A METHODOLOGY TO CLASSIFY PATIENTS IN THE MEDICINE'S CONSUMPTIONS APPLYNG DATAMART AND DATAMINING A HOSPITAL - Tapia Rivas, Ivan (2007)
The present work, provides a method for the analysis of data in the way with which the medicines in a Peruvian hospital are consumed, in order to identify some nonobservable realities or characteristics which would produce shortage of supplies or insaTIsfaction of patients, serving as a tool for the decision making on the medicine supplying in the hospital. Here techniques of datamart are complemented, of extraction and load of data, as well as algorithms of mininig suchs K-means to classify the mentioned medicine consumptions. Finally there are graphs with some extracted results from the tests.